2019
DOI: 10.7150/jca.29278
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Gynecologic and Urinary Tract Cancer with Pelvic Inflammatory Disease: A Population-Based Cohort Study

Abstract: Purpose: The aim of the study was to determine the association between pelvic inflammatory disease (PID) and breast, colorectal, gynecologic and urinary tract cancer.Methods: The source of data was a longitudinal dataset compiled by the Longitudinal Health Insurance Database 2000 (LHID2000) which was collected by the National Health Insurance program. Cases of PID, at least two outpatient visits and one admission, were diagnosed from 2000 to 2013. The data for controls, age matched women who were not diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[ 11 , 12 ]. Although surgery is often used to treat lumbar intervertebral disc herniation with prominent efficacy [ 13 ], nursing service in clinical practice is imperative to greatly consolidate the treatment efficacy [ 14 , 15 ]. Miyoshi et al [ 16 ] have found that effective rehabilitation training for patients after surgery can not only significantly improve the effect of surgery, but also facilitate the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ]. Although surgery is often used to treat lumbar intervertebral disc herniation with prominent efficacy [ 13 ], nursing service in clinical practice is imperative to greatly consolidate the treatment efficacy [ 14 , 15 ]. Miyoshi et al [ 16 ] have found that effective rehabilitation training for patients after surgery can not only significantly improve the effect of surgery, but also facilitate the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive tract infections such as bacterial vaginosis and Chlamydia trachomatis infection were reported to be associated with a decreasing risk of uterine fibroids [ 9 , 10 ]; the risk of bladder cancer was reduced among female patients with urinary tract infections but increased among male patients [ 40 ], which were consistent with our results. In contrast, Liu et al found that HPV infection was associated with an increased risk of breast cancer [ 41 ]; Lin et al and Stewart et al found that pelvic inflammatory diseases related to an increasing risk of urinary tract cancer [ 16 ] and ovarian cancer [ 42 ], respectively. This inconsistency might be explained by the fact that the intervals of lifetime estrogen exposure in these studies were shorter than that of our study; for example, in Stewart’s study, the proportion of women with multiple parity was higher [ 42 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the gynecologic malignancies were diagnosed within 1 year of PID diagnosis. 7 Another retrospective population-based study by Hsu MI et al evaluated the risk of CRC specifically with PID. The study included 19 029 women with PID, who were matched to a control group of 76 116.…”
Section: Discussionmentioning
confidence: 99%